Impact of online psychological services on academic achievement and COVID-19 fear in students with addicted parents - Hamid Heydari; Nooshin Pordelan; Simin Hosseinian; Masoud Safaei; Mohammad Khorrami (Elsevier, 2024)
Background: The use of online psychological services has shown potential in alleviating mental health concerns during the coronavirus epidemic. This study aimed to investigate the effects of online psychological services on COVID-19 fear and academic achievement among students with addicted parents. Methods: The current study is a quasi-experimental study with pretest, posttest, and control group. The statistical population of this study included all male and female students in Tehran province in 2022. In order to select the sample, the call to participate in the study was made by the social media (Telegram, WhatsApp, Instagram, LinkedIn) for two months. Then, corona fear questionnaire link was sent to the email addresses of the respondents and 120 students who met the inclusion criteria were selected as the sample of the study. In the next stage, 120 students were randomly assigned in the experimental and control groups. After 8 online sessions, 4 students from the experimental group and 5 students from the control group ended their cooperation due to personal reasons and as a result, 56 and 55 students constituted the experimental and control groups, respectively. Results: The results indicated a significant increase in academic achievement for students in the experimental group post-intervention compared to the control group. Additionally, online psychological services appeared to mitigate COVID-19 related fears. Conclusion: This study suggests that online psychological services play a pivotal role in enhancing student's mental well-being during the COVID-19 epidemic.